Management and monitoring of lithium-ion battery recharge with ESP32 - Gomez-Huaylla, Estefany; Mejía-Cruz, Luis; Paiva-Peredo, Ernesto (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Air quality is important for human health, the use of clean energy is one way to improve it. And the management and monitoring of the recharge of ion-lithium batteries used in electric vehicles and other devices requires efficient systems. The objective is to develop an intelligent electrical recharging system for lithium-ion batteries using internet of thing (IoT) technology. In this article, an electrical recharging system for lithium-ion batteries was designed and carried out, which is made up of a source, a diode bridge, L298 n driver, current sensor, a voltage divider sensor and the ESP32 microcontroller. The system determines the storage capacity of the battery and monitor it remotely via WIFI. The data is sent to a Shiftr.io server and graphically displayed on a NODE RED platform. The message queuing telemetry transport (MQTT) protocol is used to communicate the devices and decide the best time to recharge the batteries. The results show that the system works correctly and offer useful information that optimizes the charging process, it contributes to improving savings in the payment of electricity consumption and the use of clean energy. The limitations of the study are the small sample size and the lack of comparison with other similar systems.